2014
DOI: 10.1016/j.jhsa.2013.06.029
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical and Evolutionary Perspective on the Function of the Lumbrical Muscle

Abstract: The lumbrical muscles of the hand originate from the flexor digitorum profundus tendons and insert onto the lateral band of the extensor tendons. Owing to these movable attachments, the function of this muscle is difficult to visualize. To better determine the function of this muscle, we took a novel approach by considering its relative anatomy, biomechanical characteristics, and evolution. With the smallest physiological cross-sectional area in the upper extremity, the lumbrical muscles have weak motor functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 31 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…Among them, the lumbrical muscles have the greatest number of muscle spindles among upper limb muscles; therefore, although their biomechanical contribution is secondary due to their small size, they are considered to factor prominently in proprioceptive monitoring for precision movements of the fingers. 8,9 We considered that the efficient use of these intrinsic muscles enabled the grip-type holder to spare forearm muscle movement by contributing principally to stable microsurgical suturing. Releasing the needle with the grip-type needle holder requires flexion of the middle finger to pull on the trigger with the extrinsic forearm flexors of the flexor digitorum superficialis and profundus.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the lumbrical muscles have the greatest number of muscle spindles among upper limb muscles; therefore, although their biomechanical contribution is secondary due to their small size, they are considered to factor prominently in proprioceptive monitoring for precision movements of the fingers. 8,9 We considered that the efficient use of these intrinsic muscles enabled the grip-type holder to spare forearm muscle movement by contributing principally to stable microsurgical suturing. Releasing the needle with the grip-type needle holder requires flexion of the middle finger to pull on the trigger with the extrinsic forearm flexors of the flexor digitorum superficialis and profundus.…”
Section: Discussionmentioning
confidence: 99%
“…Some believe that the lumbricals contribute to the radial deviation and abduction of the digits. 2 The function of the lumbricals is determined by their origin and insertion. The lumbricals arise from the radiovolar surface of the flexor tendons at the level of the wrist and proximal palm, and, as such, they have a variable location.…”
Section: Lumbrical Musclesmentioning
confidence: 99%
“…The thenar muscles control the motion of the thumb, and the hypothenar muscles control the motion of the little finger. 1,2 The intrinsic muscles of the hand have not received much attention in the radiologic literature, despite their importance in moving the hand. [3][4][5][6][7] Prospective studies on magnetic resonance (MR) imaging of the intrinsic muscles of the hand are rare, especially with a focus on new imaging techniques.…”
mentioning
confidence: 99%
“…This information is essential for the coordination of movement [25], and it has been suggested that the sensory function of the lumbricals in the hand is more important than its motor function. Furthermore, the concentration of muscle spindles in the second and third lumbricals of primates, such as marmosets (Callithrux genus) and the Gray Langur, may reflect the importance of these digits during locomotion, whereas the high concentrations of muscle spindles in the first and second lumbricals in humans enable us to perform precision pinch movements [21]. Evolutionary considerations support that the lumbricals may have more of a sensory role than a motor function.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary considerations support that the lumbricals may have more of a sensory role than a motor function. The decrease in size of the lumbricals and the increase in the number of spindle fibers in the lumbricals could be related to the change in the use of the forelimbs from primarily locomotion in nonprimate mammals, toward feeding in some primates, and finally to tool use and precision manipulation of objects in humans [21].…”
Section: Introductionmentioning
confidence: 99%